(untitled) (The Review of Diabetic Studies, 2024)
Background: Diabetes mellitus remains one of the world’s fastest-growing chronic diseases, demanding integrated and secure healthcare systems to ensure continuity, prevention, and high-quality management. In this context, health security, information management, and nursing leadership represent interdependent pillars for achieving sustainable diabetic-care outcomes. Objective: This study aimed to assess the relationships among health-security readiness, information-management competence, and nursing leadership effectiveness within the integrated care and prevention of diabetes, emphasizing their collective impact on system integration and patient safety. Methods: A descriptive cross-sectional study was conducted among 230 nurses and nurse leaders across primary, secondary, and community healthcare settings. A validated questionnaire measured three main domains—health security, information management, and nursing leadership—using a 5-point Likert scale. Data were analyzed through descriptive statistics, Pearson correlation, and regression analysis. Results: Participants demonstrated high leadership engagement (M = 3.97 ± 0.59), moderate health-security awareness (M = 3.82 ± 0.64), and average information-management competence (M = 3.65 ± 0.71). Information-management competence emerged as the strongest predictor of integrated-care performance (β = 0.41, p < 0.001), followed by nursing leadership (β = 0.33) and health security (β = 0.27). Strong positive correlations were observed between information management and nursing leadership (r = 0.62, p < 0.001), confirming that data-driven leadership enhances system safety and diabetic-care coordination. However, gaps persisted in interoperability, staff training, and institutional security preparedness—especially in primary-care centers. Conclusion: The findings highlight that nursing leadership, information management, and health security function as a mutually reinforcing triad for achieving integrated and preventive diabetic care. Empowering nurse leaders with informatics and cybersecurity training, strengthening EHR interoperability, and standardizing security protocols are crucial for achieving health-system resilience and advancing Saudi Vision 2030’s health-transformation goals.